Carnivory maintains cranial dimorphism between males and females: Evidence for niche divergence in extant Musteloidea. (1st September 2018) - Law, Chris J.; Mehta, Rita S.
Abstract: The evolution and maintenance of sexual dimorphism has long been attributed to sexual selection. Niche divergence, however, serves as an alternative but rarely tested selective pressure also hypothesized to drive phenotypic disparity between males and females. We reconstructed ancestral social systems and diet and used Ornstein–Uhlenbeck (OU) modeling approaches to test whether niche divergence is stronger than sexual selection in driving the evolution of sexual dimorphism in cranial size and bite force across extant Musteloidea. We found that multipeak OU models favored different dietary regimes over social behavior and that the greatest degree of cranial size and bite force dimorphism were found in terrestrial carnivores. Because competition for terrestrial vertebrate prey is greater than other dietary groups, increased cranial size and bite force dimorphism reduces dietary competition between the sexes. In contrast, neither dietary regime nor social system influenced the evolution of sexual dimorphism in cranial shape. Furthermore, we found that the evolution of sexual dimorphism in bite force is influenced by the evolution of sexual dimorphism in cranial size rather than cranial shape. Overall, our results highlight niche divergence as an important mechanism that maintains the evolution of sexual dimorphism in musteloids.